Comparison of tolterodine and Solifancine in treatment of female with overactive bladder - Hefila, Nermeen Mohamed; el dayem, Tamer Mamdouh; Elfazari, Hisham Adel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: OAB (overactive bladder) is primarily a neuromuscular problem in which the detrusor muscle contracts inappropriately during bladder filling (i.e., storage phase). These contractions often occur regardless of the amount of urine in the bladder. The aim of this work is to study the effect of Solifenacin in comparison to Tolterodine in treatment of females with idiopathic over active bladder. Methods: This study included 50 patients who presented between March 2020 and February2021 to the outpatients clinic at El-Shatby maternity Hospital, Alexandria university. The patients were complaining of urinary urgency usually with urinary frequency, nocturia with or without urge incontinence. All cases were divided in two groups one of them receive Solifenacin5mg twice daily and the otherreceiveTolterodine2mg twice daily. Results: Both groups showed significant decrease in frequency number per day with p value <0.001ingroup I with Solifenacin which mean statistically significant difference between two groups. When the percentage of symptoms severity were compared between both groups, group 1 showed 53% reduction in symptoms severity while group II showed 6.67% reduction which cleared significant difference statistically in group I (p=0.001). The percentage of reduction of severity of symptoms was compared between the two groups, it showed about 60%reduction in symptoms severity in group 1while in group II only 9.7% reduction. This was statistically significant with (p<0.001) in group I with Solifenacin. Conclusions: This study suggests that Solifenacin10mg/day is more effective than Tolterodine4mg/day in reducing OAB incontinence episodes.